Pengaruh Pemasaran Melalui Konten Instagram dan Online Customer Review Shopee terhadap Keputusan Pembelian - Kusumaningrum, Imanuela Christin Anggita; Agung Pujianto; Awin Mulyati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the influence of marketing through Instagram content and Shopee's online customer reviews on consumer purchase decisions on Luxcrime products. This study uses a quantitative method with an associative type of research. The sample used was 96 respondents who had bought Luxcrime products, with incidental sampling techniques. Data was collected through an e-questionnaire and analyzed using classical assumption tests, multiple linear regressions, t-tests, and F-tests. These findings show that digital marketing strategies through social media and e-commerce can increase effectiveness in driving consumer decisions to buy products.